Effectiveness of social-emotional development programs applied in primary education: an umbrella systematic review - Moreno , Eliana M.; Montero, Ana; Armada, Jose M. (Anales de Psicología / Annals of Psychology, 2024)
Currently, the development of training programs in socioemotional skills in childhood has increased because they are considered as a valid tool for adaptation and coping with a variety of situations, both academic and personal. However, there are few studies that show a comprehensive view of available evidences. This research presents an umbrella review based on PRISMA method guidelines. It includes reviews on socio-emotional development programs applied in Primary Education with the aim of synthesizing their characteristics and compiling the main results on their effectiveness. The following databases were used: ERIC, WOS, PSYCINFO, SCOPUS and COCHRANE. After a blind peer process, 15 reviews that met the inclusion criteria were selected and analysed. Using the AMSTAR-2 and SANRA tools, it was found that 60% of secondary studies have critically low or low quality. Thirty nine programs reported in good quality reviews were identified, 51.2% presented moderate or strong evidence and reported significant effects mainly on behavioral adjustment, social and emotional competencies and academic skills. The impact of the methodological quality found and the evidences on the interpretation and generalization of the findings is discussed.